• 1. Преобразуйте в многочлен:а) (3а + 4)2; б) (2х - b)2; в) (b + 3) (b - 3); г) (5у - 2х) (5у + 2х).• 2. Упростите выражение (с + b) (с - b) - (5с2 - b2).• 3. Разложите на множители: а) 25у2 - а2; б) с2 + 4bс + 4b2.4. Решите уравнение 12 - (4 - х)2 = х (3 - х).5. Выполните действия: а) (3х + у2) (3х - у2); б) (а3 - 6а)2; в) (а - х)2 (х + а)2.6. Разложите на множители: а) 100а4 - b2 ; б) 9х2 - (х - 1)2; в) х3 + у6.

1

Ответы и объяснения

2014-03-16T10:25:57+04:00
№1 a) (3a+4)2=6a+8
б) (2x-b)2=4x-2b
в) (b+3)(b-3)= b²-9
г) (5y-2x)(5y+2x)=25y²-4x2